The association between electric scooter riding position and injury characteristics. (February 2023) - Shichman, Ittai; Shaked, Or; Factor, Shai; Ashkenazi, Itay; Elbaz, Etay; Aviv Mordechai, Reut; Khoury, Amal
Highlights: E-scooters represent a new transport modality that is smaller in size than an average motorcycle, and one with riding patterns that can be unpredictable. All shared e-scooter companies offer solely narrow-base e-scooters that force riders to use the foot behind foot riding position. Foot behind foot riding position is associated with higher rates of orthopaedic fractures. Abstract: Background: The popularity of electric scooters (e-scooters) and the shared e-scooter services as new means of transportation worldwide led to high numbers of injuries requiring emergency department (ED) visits. Private and rental e-scooters have different sizes and capabilities, offering several possible riding positions. While the rising use of e-scooters and their associated injuries have been reported, little is known about the influence of riding position on injury characteristics. The purpose of this study was to characterize e-scooter riding positions and their related injuries. Methods: E-scooters related ED admissions were retrospectively collected between June 2020 and October 2020, in a level-I trauma center. Demographics, ED presentation data, injury information, e-scooter design, and clinical course were collected and compared according to e-scooter riding position ("foot-behind-foot" vs "side-by-side"). Results: During the study period, 158 patients were admitted to the ED with e-scooter related injuries. The majority of riders used the foot-behind-foot position ( n  = 112, 71.3 %) compared to the side-by-side position ( n  = 45, 28.7 %). Orthopedic fractures were the most common injuries ( n  = 78, 49.7 %). "Foot-behind-foot" group had a significantly higher fracture rate compared to "side-by-side" group (54.4 % vs 37.8 % within group, respectively; p  = 0.03). Conclusions: Riding position is associated with different injury types, with orthopedic fracture rates significantly higher in the more commonly used "foot-behind-foot" riding position. Practical Application: These study findings suggest that the common e-scooter narrow-based design is considerably more dangerous, calling for further research to introduce safer e-scooter designs and update recommendations for safer riding positions.